PLASMIC积分对血栓性血小板减少性紫癜和弥散性血管内凝血鉴别的临床价值 (Zhonghua Xue Ye Xue Za Zhi, 2018)
OBJECTIVE: PLASMIC score was evaluated its value in differential diagnosis between the patients with thrombotic thrombocytopenic purpura (TTP) and those with disseminated intravascular coagulation (DIC). METHODS: Twenty-four patients with TTP and 41 cases with DIC were retrospectively analyzed in this study. The platelet count, average red blood cell volume, indirect bilirubin, creatinine and prothrombin time international normalised ratio were collected, and then PLASMIC scores were calculated. RESULTS: According to the risk classification of PLASMIC score, three (12.5%) TTP patients had moderate risk, and the rest 21 (87.5%) cases had high risk. In DIC patients, 92.7% cases were in low risk group, 4.9% at moderate risk, and only one case had high risk. Of these 65 patients, the sensitivity and the specificity to TTP of the high risk of the scoring system were 87.5% and 97.6%, respectively. CONCLUSION: The patients with high risk of PLASMIC score correlated well with clinical TTP diagnosis. The scoring system showed to be an excellent diagnostic model to distinguish TTP patients from those with DIC.